Key Succes Factors for Public Services in Education - Arief Rahman Hakim; Haedar Akib; Andi Cudai Nur (International Journal of Social Science and Humanity, 2024)
This study aims to identify the key success factors of public services in the education sector in Makassar City, using qualitative research. Based on the source, the types of data used are primary and secondary. Data obtained through interviews with the education office and school principals, while secondary data is data obtained from various literatures such as books, laws and other related sources. The results showed that there are two key success factors, namely supporting factors and inhibiting factors. Supporting factors are: a) there is good cooperation between the education office and the school assigned to do LINOA. b) there is motivation, psychology and a good spirit of willingness from the leadership. c) schools that are accessed by LINOA find it easy to make Star Class innovations and Recognise Potential, for LINOA support in building cross-sector cooperation. The inhibiting factors are: a) Asymmetric Information about the existence of LINOA. b) Misconceptions about creativity and innovation that are valuable from the existence of LINOA. c) Low HR competence in the era of capability. d) Little time to make innovations, finally no innovative thinking creativity.